General Development Strategies - Anon, A. (NZGA: Research and Practice Series, 1995)
Having briefly described the high country in terms of its environment, potential pasture production, and suitability of particular pasture species, we need to consider development strategies for sustainable animal production. Important points are: Type of animal Provision of winter feed Land and management requirements to grow young stock Subdivision of land into its various natural units to firhi the year round stock feed requirements Efftcient use of fertilisers General strategies of pasture development using legumes, grasses and nutrient cycling.